2016
DOI: 10.1016/j.apjtm.2016.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Study on the role of Cathepsin B and JNK signaling pathway in the development of cerebral aneurysm

Abstract: After the attack of cerebral aneurysm, proteins like Cathepsin B, Caspase-3 and p-JNK are all involved in the apoptosis of VSMCs. This process may be realized by Cathepsin B which activates the apoptosis mechanism of Caspase-3 and mediate the apoptosis of VSMC through the JNK signaling pathway. Therefore, silencing Cathepsin B gene or inhibiting the conduction through JNK signaling pathway can mitigate the apoptosis of vascular smooth muscle cells in cerebral aneurysm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Another important finding in the present study was that the ANXA3 silencing acted as an inhibitor of JNK expression, which led to the promotion of VSMC proliferation and reduced VSMC apoptosis. The proliferation and apoptosis of VSMCs were normally involved in maintaining the blood vessels, 13 the layer of which was frequently lacking in tumor vessels, promoting tumor invasion and metastasis 29 . Guo et al 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important finding in the present study was that the ANXA3 silencing acted as an inhibitor of JNK expression, which led to the promotion of VSMC proliferation and reduced VSMC apoptosis. The proliferation and apoptosis of VSMCs were normally involved in maintaining the blood vessels, 13 the layer of which was frequently lacking in tumor vessels, promoting tumor invasion and metastasis 29 . Guo et al 13 .…”
Section: Discussionmentioning
confidence: 99%
“…As a family member of mitogen-activated protein kinase (MAPK), JNK was also correlated with IA, where JNK mainly undergoes cell proliferation, migration, differentiation, apoptosis, and inflammation 12 . Recent studies have demonstrated that excessive apoptosis of vascular smooth muscle cells (VSMCs) may be an important factor for the cerebral aneurysm formation, and the JNK pathway may be the pro-apoptotic pathway of VSMCs 13 . It has been found that ANXA3 promoted the tumor formation by JNK signaling pathway activation in the liver cancer stem cells 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Statins inhibit Rho kinase activity in patients with atherosclerosis (Nohria et al., ). Moreover, a recent study showed that RhoA/ROCK signaling regulated smooth muscle phenotypic modulation and vascular remodeling (Tang et al., ) and the activation of JNK is important in the development of cerebral aneurysm (Guo et al., ). In the present study, LIG exerted an effect on suppressing AngII‐induced VSMCs migration.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, there is evidence that inhibiting inflammation in the aortic wall coupled with promoting VSMC proliferation has an essential component in the treatment an aneurysm rupture . Recent studies are acknowledged for their findings pertaining to the molecular pathogenesis of IAs that focus on VSMC activities …”
Section: Introductionmentioning
confidence: 99%
“…6 Recent studies are acknowledged for their findings pertaining to the molecular pathogenesis of IAs that focus on VSMC activities. 7,8 Serine-arginine protein-specific kinases (SRPKs) are pivotal regulators in transducing growth signals from the cell surface to the nucleus in order to regulate mRNA splicing. 9 The structure of SRPKs comprises a conserved kinase domain which is separated by a large, non-conserved insert domain approximately 250 amino acids in size.…”
Section: Introductionmentioning
confidence: 99%